A lousa digital interativa no ensino fundamental: um estudo de caso de uma escola municipal brasileira - Esteves, Rodolfo Fernandes; Souza, Cláudio Benedito Gomide de; Fiscarelli, Silvio Henrique [UNESP] (My University, 2013)
The main objective of this paper is to realize a review of literature about use of Interactive Digital Whiteboard, as a tool for improving the quality of education. We intend to show some results already reported in several studies in this area, and thus contribute to the systematization of knowledge about this resource. We found that the positive impacts of digital interactive whiteboards are specific and depend on the model followed in its implementation. Although the literature on this technology still emerging, there is evidences of good practice and positive results in all areas of the curriculum. The outcome of this research shows that to get potential benefits of digital whiteboard will be necessary, at first, to understand the process implementation and appropriation. If hardware and software of Interactive Digital Whiteboard not available and adequately used all their potential benefits not will take effect.

Este trabalho tem como foco principal realizar uma revisão da literatura sobre o uso da Lousa Digital Interativa como instrumento de melhoria da qualidade da educação. Buscamos agregar alguns resultados já divulgados em diversas pesquisas nesta área, e assim contribuir na sistematização dos conhecimentos sobre este recurso. Verificamos que os impactos positivos das lousas digitais interativas são pontuais e dependem do modelo seguido em sua implementação. Embora a literatura sobre essa tecnologia ainda é emergente, há evidências de boas práticas e resultados positivos em todo o currículo. Entendemos que para compreender os possíveis benefícios da lousa digital será necessário, em um primeiro momento compreender o processo implementação e apropriação, pois se a ferramenta não for adequadamente disponibilizada e utilizada todos seus potenciais benefícios não se efetivarão.
The interactive whiteboard as a tool to improve the quality of education an overview
Keywords: Innovation; Interactivity; Digital interactive whiteboard; Public policy; Quality of education; Inovação; Interatividade; Lousa digital interativa; Políticas públicas; Qualidade da educação